Effect of benralizumab treatment on the airway microbiome in COPD - Koirobi Haldar; Vijay Mistry; Mathew Richardson; Corinne Hamblet; Maria Jison; Michael R. Barer; Christopher McCrae; Christopher E. Brightling (ERJ Open Research)
Background One-third of patients with COPD have an eosinophilic inflammatory phenotype. Benralizumab is an afucosylated humanised monoclonal antibody that targets the interleukin-5 receptor α subunit, leading to rapid and near-complete eosinophil depletion via antibody-dependent cellular cytotoxicity. We hypothesised that benralizumab-targeted immune modulation could have an impact on the airway microbiome in COPD. The objective of the present study was to investigate the effect of benralizumab treatment on inflammation and the sputum microbiome in COPD. Methods Sputum samples from 94 COPD patients enrolled to the GALATHEA trial (NCT02138916) and randomised to receive placebo (33), benralizumab at 100 mg (29) or 30 mg (32) over 52 weeks were analysed at baseline, week 24 and at end of treatment (week 56). Sputum microbiota taxonomic profiles and diversity indices, generated from paired-end Illumina sequencing targeting the 16S rRNA gene, were used for comparative analyses. Linear mixed model analyses were applied to blood and sputum cell counts and eosinophil mediators for within- and between-treatment group analyses. Results Participants treated with 100 and 30 mg benralizumab, respectively, showed a significant reduction from baseline in both blood and sputum eosinophil counts (blood: p=1.2e-10 and p=8.8e-10; sputum p=0.03 and p=0.004) and eosinophil-derived serum mediators (eosinophil cationic protein: p<3e-09 and p<2e-08; eosinophil-derived neurotoxin: p<8e-12 and p<2e-09). No significant changes in the composition or diversity of the sputum microbiome were observed. Conclusions In this study, the airway microbiome measured in sputum was unaffected by a targeted reduction of eosinophilic inflammation with benralizumab treatment.